Effects of Asthma and Inhalation corticosteroids on the dental arch morphology in children - S S Kumar; B Nandlal (Wolters Kluwer Medknow Publications, 2012)
Background: Hereditary, environmental and developmental factors play an important role in dentofacial development, as well as the initiation of malocclusion disorder. Allergic phenomenon such as asthma that induces an alternative mode of breathing in patients is a contributing factor in development of the dental arch. Aim: Our aim in this study was to evaluate the dentoalveolar morphology in asthmatic children and to analyze the effects of asthmatic medications on the dental arch. Setting and Design : This study is centered on 44 asthmatic children aged between 6-12 years from J.S.S Hospital, Mysore. Selected variables from model analysis of the casts of the asthmatic group were subjected to comparison with those of the non-asthmatic group, which comprised of 44 non-asthmatic children. Selected parameters were arch width, arch length and palatal depth. Materials and Methods : Impressions of upper and lower arches were made with rubber based impression material. A sliding digital caliper was used to measure the casts for arch width and arch length. A palatal depth gauge was used to measure the palatal depth. Statistical Analysis : Differences in arch widths, arch lengths and palatal depths between asthmatics and non-asthmatics groups were evaluated by independent sample t-tests. Chi-square test was applied to assess the frequency of occurrence of malocclusion in the asthmatic children. Result: The results obtained revealed that the arch length and palatal depth of asthmatic group had higher values compared to that of non-asthmatic groups for both age groups (6 to 8-year-old males and females, 10 to 12-year-old males and females). Inter molar width showed a significant lower value in asthmatics in the maxillary arches of 10 to 12-year-old females. Fifty percent of the asthmatic children aged 10 to 12-years had open-bite. Children under regular medication showed significant deviation in the dentoalveolar morphology as compared to those under irregular medication. Conclusion: The present study proves a strong relation between asthma and dentoalveolar morphology.